The Impact of Women Leadership and Decision-Making on Employee Performance with Servant Leadership Style as a Moderating Variable - Novialumi, Anita; Widiawati, Kristiana; Maisaroh, Esah (IJBLE Scientific Publications Community Inc., 2024)
This study aims to examine the influence of women's leadership and decision making on employee performance, as well as the moderating impact of servant leadership style in the context of the food and beverage subsector manufacturing industry in the Greater Bekasi area. A quantitative approach was used with nonprobability sampling techniques, and data were analysed using Structural Equation Modelling (SEM), involving 219 respondents as research samples. The results showed that female leadership and decision making had a significant effect on employee performance. In addition, servant leadership style moderates the relationship between these variables, suggesting that the application of this leadership style can strengthen the positive impact of women's leadership and decision-making on employee performance. The practical implication of this study is the importance of women's leadership development and the application of servant leadership style in improving employee performance in the industrial sector under study